After years in the wilderness: development and the discourse of land claims in the new South Africa - James, Deborah (My University, 1997)
Anthropologists, it is currently claimed, can and should play a significant role in those processes of managed and haphazard social change subsumed under the heading of development (Pottier 1993). In South Africa, many anthropologists have acted - indirectly or directly - to defend the rights of communities subjected to the vagaries of the capitalist economy and to various forms of government planning. In relation to the former, they have documented the effects of labour migration and of the gradual decline in subsistence agriculture; while in relation to the latter they have looked at the social upheavals caused by population resettlement, whether these were the clear outcomes of state plans or rather more unforeseen. But a more novel and certainly more ambitious approach would be for the anthropologist's gaze to broaden, thus encompassing not only these local communities but also those who have represented, or worked to alleviate, their plight. My own analysis here is based on the discourse and rhetoric used not only by resettled people claiming restitution but also by parties - people in the "land" NGOs, in local and regional government, and in any of a number of newly-emerging consultant consortiums - who concern themselves with restoring territories to their claimants and with developing and improving these.
African Studies Seminar series. Paper presented 13 October, 1997
Keywords: Land settlement. South Africa; Right of property. South Africa